Preparation Structure and Magnetic Properties of Mn-Doped ZnO Nanoparticles Prepared by Hydrothermal Method - GÜLER, ADİL; BOYRAZ, CİHAT (SPRINGER, 2019)
In this research, manganese-doped ZnO (Zn0.99-xMnxO) nanoparticles were synthesized by hydrothermal method using the chemicals. The samples were annealed at 500 and 600 degrees C to figure out the optimum annealing temperature characterized by differential thermal analysis (DTA) method. Simultaneously with DTA analysis, the possible weight loss was observed by thermal gravimetric (TG) method and categorized the lost chemicals with varying temperature regions. The crystal structure with lattice parameters and the phases were determined by X-ray diffraction method. Microstrain (epsilon), stress (sigma), the dislocation density (delta), the locality of the atoms and their displacements (u), and the bond length (L) values were calculated by making use of lattice parameters. The particle morphologies were monitored by scanning electron microscope (SEM) technique and the elemental compositions of the samples were investigated and found that all peaks belong to Zn, Mn, and O elements. The magnetic properties of the samples were revealed using Quantum design PPMS measurement system and correlated with structural properties.
Keywords: Zinc oxide; Hydrothermal method; Magnetic properties; ROOM-TEMPERATURE FERROMAGNETISM; CO